Reactivation and persistence of human herpesvirus-8 infection in B cells and monocytes by Th-1 cytokines increased in Kaposi's sarcoma. - Monini, Paolo; Colombini, Sandra; Stürzl, Michael; Goletti, Delia; Cafaro, Aurelio; Sgadari, Cecilia; Buttò, Stefano; Franco, Marina; Leone, Patrizia; Fais, Stefano; Leone, Pasqualina; Melucci-Vigo, Gianna; et al. (Blood, 1999)
Patients with Kaposi's sarcoma (KS) have a human herpesvirus-8 (HHV-8) load higher than patients without KS and present a CD8(+) T-cell activation with production of Th1-type cytokines both in tissues and peripheral blood mononuclear cells (PBMC). Because in tissues of KS patients detection of inflammatory cytokines (IC) can precede detection of HHV-8 DNA and because signs of immunoactivation and/or dysregulation can precede KS development, we investigated the effect of IC on HHV-8 infection. To achieve this goal, PBMC and purified cell populations from 45 patients with KS and 45 patients at risk of KS were analyzed for HHV-8 DNA and/or gene expression and for cell survival, growth, and phenotype before or after culture with or without the IC increased in KS. The results indicate that PBMC that are polymerase chain reaction (PCR)-positive at day 0 generally loose the virus upon culture. However, the presence of IC maintains HHV-8 DNA load in cultured cells. In addition, IC increase viral load to detectable levels in PBMC from serologically positive patients that were PCR-negative before culture. gamma Interferon is sufficient for these effects, whereas tumor necrosis factor and interleukin-6 have little or no activity. The increase of HHV-8 DNA by IC is observed after short-term (7 days) or long-term (28 days) culture of the cells and occurs in one or both of the two circulating cell types that are infected in vivo: B cells and monocytes. In both cases it is associated with lytic gene expression, suggesting that virus reactivation is one of the most likely mechanisms for the effect of IC on virus load. However, IC have also effects on the cells target of HHV-8 infection, because they increase B-cell survival and induce the growth and differentiation of monocytes into KS-like spindle cells with markers of endothelial macrophages. Because cells with markers of endothelial macrophages are present in blood and lesions from KS patients and are infected by HHV-8, these data may explain the high HHV-8 load associated with KS development and suggest that infected monocytes may carry the virus to tissues, transmit the infection, or differentiate in loco in spindle cells with endothelial macrophage markers.